PENATAAN ULANG WILAYAH KERJA RESORT MENGGUNAKAN SPATIAL MULTI-CRITERIA ANALYSIS (Studi Kasus di Taman Nasional Gunung Ciremai) - , Nova Indri Hapsari; , Dr. Ir. Lies Rahayu W.F., MP. ([Yogyakarta] : Universitas Gadjah Mada, 2013)
The first step of effectiveness national park using resort-based management (RBM) system is structuring management unit area. The goal of RBM is to run management of national park effectively and more systematic by dividing the area into management units which is support staff of national park working profesionals in fixed area. RBM applied in Gunung Ciremai Natioanl Park (GCNP) since 2009 however the system not support management optimally. Based on evaluation management effectiveness in presenting low value with score of effectiveness 38 from the highes score 100, shows that implementation management not yet affect optimaly, for the reason management of TNGC need evaluation of RBM implementation. Step of RBM implementation including improvement management unit area, strengthening institutional and developing national park system information. This study focuses at improvement management unit are as fundamental aspect in resort-based management (RBM). To improvement resort management unit area require various criteria such as of the region's natural resources, social and economic aspects as well as aspects of resource management organization. National park is a common pool of resources with unique characteristics where the interests of the various parties, and ecological interests also included in the national park ecosystem. For the some reasons the study using multi-criteria analysis with Spatial AHP method. The methods integrates the physical characteristics of the region and important aspects of park management to make decision. The result present five criteria to improvement management area unit of GCNP and the criteria consisting of physical criteria, potential threats, ecological, economic and socio-cultural. The result of spatial-AHP analysis from experts judgment comparison presenting the weight for each criteria was: physical (0.29), threat (0.36), ecology (0.14), the economy (0.07), and social (0 , 13). Evaluation of management unit area in GCNP based on the weight of each criteria presenting revision number and extent of the work area from 11 to 5 area with various extents as follows: Resort Pasawahan (4112 ha)